Cooperation between airports: A focus on the financial intertwinement of European airport operators. (June 2018) - Bringmann, Katja; De Langhe, Katrien; Kupfer, Franziska; Sys, Christa; Van de Voorde, Eddy; Vanelslander, Thierry
Abstract: Recent airport cooperation initiatives and the lack of detailed research on the cooperation between airports suggest a research gap on this topic. The present study therefore investigates cooperative arrangements between European airports by focusing on their financial intertwinement. Social network analysis tools are used to examine the structural patterns of financial relationships in the airport sector, while a multiple regression quadratic assignment procedure (MRQAP) is applied to measure the impact of financial path dependency and spatial patterns on the occurrence of investment ties. The findings indicate a high degree of stability in investment relations in the airport industry over time. Furthermore, it is suggested that the formation of interorganisational linkages is facilitated by spatial proximity. Highlights: Financial linkages between European airports are investigated. Social network analysis and MRQAP are applied to measure financial path dependency. Investment relations in the airport industry are highly stable over time. Formation of interorganisational linkages is facilitated by spatial proximity.